Short-Term Effect of Convenience Meal Intake on Glycemic Response and Satiety among Healthy College Students in South Korea - Jang, Eunji; Lee, Jeunghyun; Lee, Sukyeong; Kim, Mi-Hyun (Clinical nutrition research, 2017)
This study examined the effect of convenience meals purchased at convenience stores on glycemic response and satiety in healthy college students. A total of 9 non-obese volunteers (4 males and 5 females) aged 20 to 24 years participated in this study. On 3 separate days, participants consumed a standard diet (cooked rice and side dishes), type 1 convenience meal (kimbap and instant ramen), and type 2 convenience meal (sweet bread and flavored milk). Capillary blood-glucose response and satiety were measured every 30 minutes for 2 hours after consuming the 3 different test meals. Although mean fasting glucose levels were not different, glucose levels at 30 minutes and 120 minutes after the type 1 convenience meal intake were significantly higher than those in the standard meal (p < 0.05, p < 0.01). Total glucose response was higher after consumption of the type 1 convenience meal, followed by the type 2 convenience meal and standard meal (p < 0.05). Though the type 2 convenience meal contained higher calorie than the other meals, satiety of the type 2 convenience meal was lowest at 30 minutes and 60 minutes after consumption (p < 0.01, p < 0.05). This pilot study suggests that convenience meals may increase glycemic response or induce higher calorie intake with low satiety compared with nutritionally balanced Korean style meal.